227k views
0 votes
Adding and subtracting functions f (n ) = −2n^3 + 3n^2g(n) = −2n − 4 Find f (n )+ g(n)​

User Mauvm
by
5.1k points

2 Answers

1 vote

Answer: f(n) + g(n) = -2n^3 + 3n^2 - 2n - 4

Step-by-step explanation:

Honestly i dont know if that answer is correct

im just trying to gain points

but i copied it from someone else

2n +5y=6 eggs

User Sorin Trimbitas
by
4.6k points
4 votes
Answer: f(n) + g(n) = -2n^3 + 3n^2 - 2n - 4

Step-by-step explanation:

f(n) + g(n) = (-2n^3 + 3n^2) + (-2n - 4)
f(n) + g(n) = -2n^3 + 3n^2 - 2n - 4
User Don Ho
by
4.3k points